2018
DOI: 10.1002/elan.201800360
|View full text |Cite
|
Sign up to set email alerts
|

Uricase Based Enzymatic Biosensor for Non‐invasive Detection of Uric Acid by Entrapment in PVA‐SbQ Polymer Matrix

Abstract: In this work, an electrochemical approach using uricase (UOx) as an enzyme to detect uric acid (UA) for wound monitoring has been reported. UOx was entrapped in poly (vinyl alcohol) N‐methyl‐4(4’‐formylstyryl) pyridinium methosulfate acetal (PVA‐SbQ), a cationic polymer matrix. The polymer‐enzyme ratio for immobilization was calculated as 53.2 μg cm−2 : 0.25 U cm−2. UA was detected both optically as well as electrochemically. A redox electron shuttle, ferrocene carboxylic acid (FCA) was used to facilitate elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…[ 31,32 ] In this process, the polymer matrix can not only physically entrap the enzymes on the electrode but also improve their immobilization via electrostatic interactions between negatively charged amino acid chains of enzymes and positively charged styrylpyridinium side chains in PVA–SbQ. [ 33,34 ] Fluorescence microscopy and SEM characterizations demonstrated that the shedding of the enzyme from the electrode was remarkably reduced after rinsing (Figure 2e,f; Figures S9 and S10, Supporting Information). Based on the above advantages, the bioelectrocatalytic performance of both O 2 reduction and glucose oxidization can be effectively enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…[ 31,32 ] In this process, the polymer matrix can not only physically entrap the enzymes on the electrode but also improve their immobilization via electrostatic interactions between negatively charged amino acid chains of enzymes and positively charged styrylpyridinium side chains in PVA–SbQ. [ 33,34 ] Fluorescence microscopy and SEM characterizations demonstrated that the shedding of the enzyme from the electrode was remarkably reduced after rinsing (Figure 2e,f; Figures S9 and S10, Supporting Information). Based on the above advantages, the bioelectrocatalytic performance of both O 2 reduction and glucose oxidization can be effectively enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…7, represented by yellow and green arrows. There is a dynamic balance between monosodium urate and synovial fluid, and the separated monosodium urate ion immediately produces a chemical reaction when it encounters uricase [13]. Although monosodium urate is difficult to dissolve, it still has dissolution equilibrium with the aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, tophi are formed by the deposition of MSU. Monosodium urate is formed by replacing H + with Na + in the molecular structure, and this molecule is less soluble and thus more likely to form precipitates and deposits in human body [12,13]. There is no significant difference in molecular structure between the two compounds and the core and functional groups of the two compounds are similar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there are many ways to modify enzymes on electrochemical electrodes, including physisorption, chemisorption, and entrapment [ 102 ]. RoyChoudhury et al [ 103 ] reported a flexible wearable electrochemical sensor for uric acid detection based on UOx, and the UOx was entrapped in poly(vinyl alcohol) N -methyl-4(4′-formylstyryl) pyridinium methosulfate acetal, a cationic polymer matrix. In addition, ferrocene carboxylic acid (FCA) was also introduced to assist the electron transfer between the active site of the enzyme and the surface of the sensor.…”
Section: Key Wound Marker Detectionmentioning
confidence: 99%